Use of N-acetylcysteine as treatment adjuvant regulates immune response in visceral leishmaniasis: Pilot clinical trial and in vitro experiments - Magalhães, Lucas Sousa; Melo, Enaldo Vieira; Damascena, Nayra Prata; Albuquerque, Adriana Cardoso Batista; Santos, Camilla Natália Oliveira; Rebouças, Mônica Cardozo; Bezerra, Mariana de Oliveira; Louzada da Silva, Ricardo; de Oliveira, Fabricia Alvisi; Santos, Priscila Lima; da Silva, João Santana; Lipscomb, Michael Wheeler; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
Visceral leishmaniasis is a vector-borne disease caused by Leishmania parasites. The balance of effective immune response and parasite favorable response to treatment is crucial to disease evolution. Pentavalent antimonial compounds are major drugs used to treat visceral leishmaniasis, despites numerous adverse effects and limitations of use. N-acetylcysteine is a well-known compound that has been used to treat many conditions. Thus, the present study aimed to test the effect of N-acetylcysteine as adjuvant treatment to visceral leishmaniasis. The present work include: a pilot blinded and randomized clinical intervention study (NCT01138956, https://clinicaltrials.gov/ct2/show/NCT01138956) and experimental in vitro study. Patients were treated with meglumine antimoniate only or meglumine antimoniate plus N-acetylcysteine. In vitro experiments were made using PBMC cells from healthy donors. The results demonstrated that patients treated with NAC have higher sCD40L in sera during treatment and the levels of sCD40L was negatively correlated to IL-10 levels. Data estimation showed negative correlation between sCD40L levels and spleen size in LV patients. Patients in Test or Control group had similar results in laboratorial and clinical parameters. In vitro experiments showed that NAC treatment of SLA stimulated PBMC reduces the frequency of monocytes producing IL-10 and reduces the frequency of T CD4+ and CD8+ cells expressing inflammatory cytokines. Taken together, the results suggests that NAC treatment may modulate de immune system response in LV patients and this places it as a candidate as adjuvant to antimony therapy for visceral leishmaniasis.